Necropolitics of winds: social determination of mental health in the face of exposure to wind power enterprises in rural communities of Pernambuco - Cazeiro, Felipe; Gomes, Wanessa Silva; Costa, André Monteiro; Costa, Andrei Junior da; Silva, Rian Rafael; Silva, Maria Eduarda Virginio Gomes da; Teixeira, Sara Regina da Silva; Silva, Vivian Karla Sousa da; Santos, Claudia Danielle Pereira; Silva, Diogo Alexandre; et al. (Sustainability in Debate, 2025)
The implementation of wind farms produces transformations in and around communities, causing diverse impacts in multiple areas, revealing vulnerability processes. This research aimed to understand these processes in rural communities in Pernambuco, Brazil, due to these projects. This quantitative and qualitative action research was conducted through semi-structured interviews, with health assessments using instruments, tests, and audiometry. We adopted content analysis to analyse the data and strengthen the struggle of these communities. To understand this persistent backdrop of violence, the research employs necropolitics as per Achille Mbembe (2020) and the social determination of health, as per Jaime Breilh (2006, 2013). We observed that the arrival and operation of wind turbines coincided with the emergence and deterioration of health signs and symptoms, especially mental health. Therefore, caution is urgently needed when planning and building wind farms, as such health problems can be temporary or permanent, leading the local community to constant distress and even a lack of will to live.